Acta Historiae Neerlandicae/Studies on the History of the Netherlands VIII - Dekker, C. author. aut Link
VII, 201 p.
Keywords: Volume VIII of Acta Historiae Neerlandicae again presents studies on the history of the Low Countries which it is hoped will be of interest to foreign scholars. The intention has been to deal with a fairly long period, and many differing aspects, of the subject. So institutional, political, economic, social and cultural history all receive a fair share of attention, and together the studies cover a considerable number of centuries. It is, however, striking to note how even this restricted number of studies reflects prevailing viewpoints among today's Low Countries' historians. Clearly there is considerable stress on economic and social questions. Traditional studies such as those of former Belgian historians on medieval history, or those of the Dutch on the seventeenth century, are now giving way to works that are problem directed. Power structures, the position of the bourgeoisie, reactions of the intelli gentsia and theologians to societal problems, have now more attraction for scholars than the glories of late medieval wealth in Flanders or Holland's Golden Age. Terms such as Guerilla warfare, Struggle, Depression, typify today's critical approach to society in general.